Pakistan Strategy Support Program (PSSP) - International Food Policy Research Institute (International Food Policy Research Institute, 2011)
Pakistan Strategy Support Program (PSSP), launched in July 2011, is a flexible country-led and country-wide policy analysis and capacity strengthening program. The program provides analytical support on a range of economic policies affecting agricultural growth and food security in the country.